1996
DOI: 10.1002/jlb.60.2.174
|View full text |Cite
|
Sign up to set email alerts
|

Human type II phospholipase A2-induced Mac-1 expression on human neutrophils

Abstract: To investigate the effect of type II phospholipase A2 (PLA2-II) on neutrophil function, we assessed the Mac-1 (CD11b/CD18) expression on human neutrophils by flow cytometry after incubation of the cells with human PLA2-II. PLA2-II at a concentration of 10 microg/mL increased the Mac-1 expression by 150% compared with unstimulated cells at 30 min and after. Under these conditions PLA2-II increased the exocytosis from secretory vesicles but not from azurophilic, specific, or gelatinase granules. The results sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Activation of other cell types by PLA 2 -IIA has been reported to be promoted by generation of lysophospholipids [28,33]. On the other hand, PLA 2 -IIA induced Mac-1 expression on human neutrophils at least partly via the generation of arachidonic acid [13]. From these findings, PLA 2 -IIA may induce diverse cell functions on many cell types via the liberation of various fatty acids and lysophospholipids.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Activation of other cell types by PLA 2 -IIA has been reported to be promoted by generation of lysophospholipids [28,33]. On the other hand, PLA 2 -IIA induced Mac-1 expression on human neutrophils at least partly via the generation of arachidonic acid [13]. From these findings, PLA 2 -IIA may induce diverse cell functions on many cell types via the liberation of various fatty acids and lysophospholipids.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, several cytokines including IL-3, IL-4, IL-5, IL-13, and GM-CSF are believed to promote survival and eosinophil activation such as CD69 expression over 2-4 h after in vitro stimulation [1,[16][17][18] We demonstrated in the present study that catalytic activity of PLA 2 -IIA was essential for induction of CD69 expression on human eosinophils. Mac-1 expression and degranulation by PLA 2 -IIA in neutrophils and T lymphocyte activation by PLA 2 -IIA are also mediated by catalytic activity of PLA 2 -IIA [13,28]. On the other hand, Murakami et al found that PLA 2 -IIA caused mast cells to release histamine without generation of prostaglandin D 2 and this effect was not blocked at all by EDTA which completely inhibited the catalytic activity [29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations